Management of Refractory Bleeding at the Duodenal Bulb Post‐Trauma Using OTSC Combined With Interventional Embolization: A Case Report - Qing Chen; Shifeng Shao (Clinical Case Reports)
ABSTRACT Multiple traumas can lead to acute gastrointestinal mucosal erosion or ulcers, typically presenting as upper gastrointestinal bleeding, while perforation occurs rarely. Rebleeding poses a serious threat to life. Standard treatments include endoscopic electrocoagulation, tissue adhesives, and titanium clips. We report a case of a 39‐year‐old woman with post‐traumatic stress ulcer bleeding successfully managed using a combination of over‐the‐scope clip (OTSC) placement and interventional embolization. This case demonstrates the effectiveness of OTSC combined with embolization in controlling post‐traumatic ulcer bleeding and preventing recurrence.